Colorimetric-based concentration measurement of manganese ions using spectroscopy approach / Nurul Hidayah Ali, Mohamed Syazwan Osman, Fatin Izyani Mohamad Robi, Mohd Rumaizan Maidan Dali, Mohamad Faizal Abd Rahman - Ali, Nurul Hidayah; Osman, Mohamed Syazwan; Mohamad Robi, Fatin Izyani; Maidan Dali, Mohd Rumaizan; Abd Rahman, Mohamad Faizal (Universiti Teknologi MARA Shah Alam, 2023)
This paper presents the spectroscopy analysis of manganese ions (Mn2+) to investigate the correlation between its concentration and optical absorbance at different wavelength spectra. This work was performed as a preliminary work to establish guidelines and references for future work in developing a monochromatic light-based colorimetric system for concentration measurement of Mn2+. The samples were prepared at the concentration range of 0.2-1.0 ppm using a colorimetric reagent (i.e., 0.1 % PAN solution) that produced an orange-based coloured solution. Qualitative analysis was performed to obtain the absorbance spectra, which are significant in identifying the suitable colour of monochromatic light (e.g., LED), as well as to predict the settling time for steady-state condition before the measurement could be taken. The results showed that for the range of concentration studied, the blue to cyan region gives the best absorbance with peak absorbance wavelength occurred at around 495 nm. Testing at the time interval between 30 and 90 min after sample preparation also gives the indication of the steady-state condition for a complete colorimetric reaction. Then, quantitative analysis was performed to obtain a standard calibration curve that relates optical absorbance and Mn2+ concentration.